Haemorrhoids or anal melanoma, importance of preoperative histopathological examination: a case report - Sherwani, Rana K.; Kumar, Amit; Raza, Mohammad H. (Polish Journal of Pathology, 2010)
Haemorrhoids are the most common lesion affecting the anorectal region, whereas anal melanoma constitutes only 1% to 3% of all malignant tumours of anal canal. The clinical presentations of bleeding per rectum, altered bowel habits and a protruding mass are common to both. We report a case of a female with classical clinical presentation of prolapsed haemorrhoids which on histopathological evaluation was found to be malignant melanoma. The case highlights the significance of exact diagnosis prior to any surgical intervention.